Use of diffusion tensor imaging in distinguishing neoplastic and infective intra-axial brain lesions: An intergroup and etiology wise inter sub-group analysis - Experience from a tertiary health care center in Northern India - Sukriti Kumar; Krishna Yadav; Neera Kohli; Manish Gutch; Neeraj Kumar; Ankur Bajaj; Anit Parihar (Wolters Kluwer Medknow Publications, 2023)
Background: Neoplastic and infective brain lesions may present as imaging mimickers. This study aims to help differentiate between etiology of lesions based on diffusion tensor imaging (quantitatively and qualitatively). Method: DTI was performed in 50 patients (12 - metastases,13 - high grade glioma,13 - tuberculoma, 12 - Neurocysticercosis). Lesional and perilesional Fractional anisotropy (FA) and mean diffusivity (MD) values were calculated. Lesional and perilesional mean FA and MD values were compared by using Student's 't'-test. Result: Mean FA values in the perilesional area of neoplastic lesions were found to be significantly higher (0.17±0.12 vs. 0.08±0.02), P < 0.001) in comparison to infective lesions. Mean MD values in the perilesional area of infective lesions were found to be significantly higher (1.51±0.22 vs. 1.20±0.33x10-3mm2/sec, P < 0.001) in comparison to neoplastic lesions. Perilesional FA was found to be significantly higher and perilesional ADC to be significantly lower in High Grade Gliomas (HGG) when compared with Metastasis, Tuberculomas or Neurocysticercosis. Infective group showed significantly higher prevalence of displacement of white matter tracts (60%) and the neoplastic group showed significantly higher prevalence of the disruption (40%). Conclusion: FA and MD values from the lesion and from perilesional region are helpful in differentiating among brain lesions. Fiber tracking along with quantitative parameters is helpful in determining type of involvement of tracts, thus helping in prognostication.